Hubungan Pengetahuan dan Sikap dengan Perilaku Caring Perawat di Rumah Sakit - Sri Rahayu (Universitas Faletehan, 2018)
Caring is a nursing action that puts the nurse caring towards the clien. In addition, caring to be the core of nursing care. This study aimed to determine factors associated with caring behavior of nurses. This study design was quantitative with cross sectional. This study was conducted at dr.Dradjat Prawiranegara Serang Hospital with 51 respondents. The statistical test showed that education level of nruse was not significant associated with caring behavior (p value 0.264), while knowledge and attitude of caring were significantly associated (p value <0,001). Caring behaviour can be affected by knowledge and attitude of nurse. Nurses who have good knowledge and attitude made good caring behaviours too.